Size distribution studies of 137Cs in river water in the Abukuma Riverine system following the Fukushima Dai-ichi Nuclear Power Plant accident. (January 2015) - Sakaguchi, Aya; Tanaka, Kazuya; Iwatani, Hokuto; Chiga, Haruka; Fan, Qiaohui; Onda, Yuichi; Takahashi, Yoshio
Abstract: The occurrence of 137 Cs in size fractionated samples in river water from the Abukuma River system, (the Kuchibuto and Abukuma Rivers, five sampling events for three sites) was studied from June 2011 – approximately some three months after the Fukushima Dai-ichi Nuclear Power Plant (FDNPP) accident until December 2012. The total concentration of 137 Cs (mBq/L) in river water was generally high at the upper stream site in the Yamakiya District within the evacuation/off-limits zone. The 137 Cs concentration was about 1 Bq/L for the first sampling campaign (June 2011) at all sites, but then decreased substantially to about one-tenth of that by the time of a second sampling campaign (November or December 2011). The 137 Cs in the <0.45 μm fraction was present exclusively as a dissolved species rather than as a species adsorbed on suspended solids or complexed with organic materials. The contribution of the dissolved fraction ranged from 1.2 to 48.9% (averaged 20%) of the total concentration of 137 Cs throughout the observation period. The maximum contribution of 137 Cs was found in the silt size fraction (3–63 μm), which can be explained by the relatively large K d values and the suspended solids (SS) concentration of this size fraction. Although the concentration (Bq/g) of 137 Cs ineach size fraction did not show any significant trends and/or variations for any of the sampling campaign, K d values for each site increased with time. Furthermore, it was found that the K d values decreased with distance from the headstream in the off-limits zone. Thus, the data acquired in this study give an overview of the radiological situation for Fukushima including temporal and spatial variation of radiocaesium in a natural riverine system, within a few years after the accident. Highlights: The 137 Cs in the <0.45 μm fraction was present as the dissolved species. The contribution of the dissolved fraction was averaged 20% of the total 137 Cs conc. The maximum contribution of 137 Cs was in the silt size fraction (3–63 μm). 137 Cs conc. (Bq/g) in each size fraction did not show any significant temporal trends. K d values of 137 Cs in each site increased with time after FDNPP accident.